Definition of rational method of extraction of stone monoliths for capital trenches - Коробийчук, Валентин Вацлавович; Иськов, Сергей Станиславович (Technology audit and production reserves, 2013)
The problems and issues that arise during the mechanical method of separating the monolith from the array are considered. For example, at what angle to drill or cut the vertical plane of the monolith, which take the optimal size of the monolith, what mechanisms or tool to use in the separation of the monolith from the array. In all cases, the need to move the monolith or upset, it is this specific problem discussed in our publication. The length of the monolith takes 2 m in all cases, the volume of the monolith with decreasing trench increased. The publication efforts that are necessary for monolith tipping or moving away from the monolithic array, depending on the angle of drilling or cutting the monolith back are calculated. The optimal drill angling the monolith back to the maximum slope of the capital trench is defined.